Impact of the Proline Residue on Ligand Binding of Neurotensin Receptor 2 (NTS2)-Selective Peptide-Peptoid Hybrids - Held, Cornelia; Hübner, Harald; Kling, Ralf; Nagel, Yvonne A.; Wennemers, Helma; Gmeiner, Peter (ChemMedChem, 2013)
To investigate the binding mode and structure-activity relationships (SARs) of selective neurotensin receptor2 (NTS2) ligands, novel peptide-peptoid hybrids that simulate the function of the endogenous ligand were developed. Starting from our recently described NTS2 ligands of type 1, structural variants of type 2 and the metabolically stable analogues 3a,b were developed. Replacement of the proline unit by a collection of structural surrogates and evaluation of the respective molecular probes for NTS2 affinity and selectivity indicated similar SARs as described for NT(8-13) derivatives bound to the subtype NTS1. Peptide-peptoid hybrids 2d, 3a,b showed substantial NTS2 binding affinity (K=8.1-16nM) and 2400-8600-fold selectivity over NTS1. The thiazolidine derivative 3b showed metabolic stability over 32h in a serum degradation assay. In an inositol phosphate accumulation assay, the neurotensin mimetics 3a and 3b displayed an inhibition of constitutive activity exceeding 1.7-2.0times the activity of NT(8-13). The fluorinated derivative 3a could afford attractive opportunities to detect NTS2 by F magnetic resonance imaging. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.